2022
DOI: 10.1186/s12905-022-01827-6
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal tRF-Leu-AAG-001 derived from mast cell as a potential non-invasive diagnostic biomarker for endometriosis

Abstract: Background The diagnosis of endometriosis (EMs) is still based on laparoscopic observation. This study tries to verify whether exosomal tRNA-derived fragments (tRFs) in leucorrhea can be used as non-invasive diagnostic markers. Methods Endometrial tissues and leucorrhea were sampled from women hospitalized in Ningbo University Affiliated Hospital from January 2021 to July 2021 with (n = 26) and without endometriosis (n = 25). Exosomes were isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…( 52 ) analyzed tRFs in blood samples and identified 11 differentially expressed molecules with prognostic value for non–small cell lung cancer. Other studies expanded the potential of tRF-based diagnostics in liver ( 53 ), gastric ( 54 ) and colorectal cancers ( 55 ), as well as in disorders as diverse as autoimmune nephritis ( 56 ), Parkinson’s disease ( 57 ), endometriosis ( 58 ), and osteoporosis ( 59 ).…”
Section: Therapeutic Potential Of Trnasmentioning
confidence: 99%
“…( 52 ) analyzed tRFs in blood samples and identified 11 differentially expressed molecules with prognostic value for non–small cell lung cancer. Other studies expanded the potential of tRF-based diagnostics in liver ( 53 ), gastric ( 54 ) and colorectal cancers ( 55 ), as well as in disorders as diverse as autoimmune nephritis ( 56 ), Parkinson’s disease ( 57 ), endometriosis ( 58 ), and osteoporosis ( 59 ).…”
Section: Therapeutic Potential Of Trnasmentioning
confidence: 99%
“…For example, Zhang et al revealed that plasma exosomal tRF-25-R9ODMJ6B26, tRF-38-QB1MK8YUBS68BFD2, and tRF-18-BS68BFD2 might be diagnostic biomarkers for osteoporosis detection ( Zhang et al, 2018 ). Mast cell-derived exosomal tRF-Leu-AAG-001 may have a promotion function in inflammation and angiogenesis and leucorrhea exosomal tRF-Leu-AAG-001 might be diagnostic biomarkers for endometriosis ( Li et al, 2022 ). Alveolar macrophage-derived exosomal tRF-22-8BWS7K092 could prompt acute lung injury through the ferroptosis pathway ( Wang et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…At least 1449 mRNAs, 938 lncRNAs, 39 miRNAs, and 61 competing endogenous RNAs (ceRNAs) were identified to display differential expression patterns in EVs derived from endometrial stromal cells (ESCs) of patients without EMs compared to ESCs of patients with EMs, including ESCs from ovarian endometrioma and those from eutopic endometrium (27). Another study found 63 up-regulated and 45 down-regulated tiRNAs and tRFs in ectopic tissue EVs from EMs (28). It was also found that lncRNAs MEG8, SNHG25, LINC00293 and RP5-898J17.1 were down-regulated, while lncRNAs LINC00998, PVT1, and RP4-561L24.3 were significantly up-regulated in ectopically diseased EVs from EMs patients (29).…”
Section: Evs Are Involved In Mediating Emsmentioning
confidence: 93%